Estimating Congenital Cardiac Surgical Need in Africa Using Geographic Distribution of Surgeons - Jordan Leith; Lamia Harik; Kevin R. An; Taylor Brashear; Robert N. Peck; Castigliano M. Bhamidipati (Annals of Global Health)
Background: Access to congenital cardiac surgical care in Africa is limited and poorly characterized, with current assessments examining only the number of surgeons in individual countries compared to their respective national population. Objective: To characterize geographic catchment areas in Africa served by the nearest congenital cardiac surgeon(s), estimate patient travel distance, and map both the incidence and unmet surgical need due to congenital heart disease (CHD). Methods: Subnational population, CHD incidence, surgeon, and geographic data were collected from credible, publicly accessible sources. Quantum Geographic Information System was used to create a subnational map of Africa and conduct nearest neighbor analyses to determine the location and distance of each subnational region’s nearest cardiac surgeon. Catchment areas were defined and characterized. Incident CHD cases and surgical needs due to CHD were calculated and mapped at the subnational level across Africa. Findings: There were 779 subnational regions from 54 countries included in this analysis. Africa was estimated to have 290 congenital cardiac surgeons located in 63 subnational regions corresponding to 63 catchment areas and 1,097,388 incident CHD cases annually. The average travel distance to a congenital cardiac surgeon was 324.40 km (201.57 miles). The ratio of incident CHD to total surgical case capacity was 20.79. Congenital cardiac surgical need was not limited to areas of high incidence and was compounded by distance to the nearest surgeon, with the greatest need occurring in the Congo Basin and Horn of Africa. Conclusions: Access to congenital cardiac surgery is limited in Africa with the capacity to surgically treat less than 5% of annual CHD cases. Surgical need is exacerbated by the geographic distribution of surgeons, which requires patients to travel great distances.